Improvised Explosive Devices: Pathophysiology, Injury Profiles and Current Medical Management. Issue 4 (1st December 2009) - Ramasamy, Arul; Hill, AM; Clasper, JC
Abstract : The Improvised Explosive Device (IED), in all its forms, has become the most significant threat to troops operating in Afghanistan and Iraq. These devices range fromrudimentary homemade explosives to sophisticated weapon systems containing high-grade explosives. Within this broad definition they may be classified as Roadside explosives and blast mines, Explosive Formed Pojectile (EFP) devices and Suicide bombings. Each of these groups cause injury through a number of different mechanisms and can result in vastly different injury profiles. The "Global War on Terror" has meant that incidents which were previously exclusively seen in conflict areas, can occur anywhere, and clinicians who are involved in emergency trauma caremay be required tomanage casualties fromsimilar terrorist attacks. An understanding of the types of devices and their pathophysiological effects is necessary to allow proper planning of mass casualty events and to allow appropriate management of the complex poly-trauma casualties they invariably cause. The aim of this review article is to firstly describe the physics and injury profile from these different devices and secondly to present the current clinical evidence that underpins their medical management.